1989
DOI: 10.1039/f19898501351
|View full text |Cite
|
Sign up to set email alerts
|

In situ scanning tunnelling microscopy of a platinum {111} surface in aqueous sulphuric acid solution

Abstract: An in situ scanning tunnelling microscope was applied, for the first time, to a single-crystal platinum { 1 1 l} surface both before and after electrochemical potential cycling in aqueous sulphuric acid solution. The single-crystal Pt{ 11 l} was annealed in a flame near 1100 "C for 1 min and then quickly brought into contact with pure water. It was not possible to see any particular structures on the fire-annealed single crystal. It is shown that the fire-annealing procedure can produce an almost completely at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…Itaya and coworkers [56][57][58] performed continuously in situ STM measurement on polycrystalline Pt [56] and Pt(lI1) [57, 581 in aqueous sulfuric acid solution. They investigated the surface changes of polycrystalline Pt with electrode potential scanning from 0.4 V to -0.23V in 0.1 M H2S04 solution [56].…”
Section: Crystal and Polycrystalline Pt Electrodementioning
confidence: 99%
“…Itaya and coworkers [56][57][58] performed continuously in situ STM measurement on polycrystalline Pt [56] and Pt(lI1) [57, 581 in aqueous sulfuric acid solution. They investigated the surface changes of polycrystalline Pt with electrode potential scanning from 0.4 V to -0.23V in 0.1 M H2S04 solution [56].…”
Section: Crystal and Polycrystalline Pt Electrodementioning
confidence: 99%
“…In the last decades, many spectroscopic and microscopic techniques have been adapted and developed by electrochemists to study the multi‐electron processes occurring on electrode surfaces as well as to track changes in surface composition, structure, and morphology. EC‐STM (Electrochemical Scanning Tunneling Microscopy), LEED (Low‐Energy Electron Diffraction) and AES (Auger Electron Spectroscopy) are examples of those commonly accepted surface science techniques adapted for electrochemistry . However, LEED and AES require ultra‐high vacuum (UHV) conditions to operate and involve sample transfer from liquid electrolyte to UHV, which increases the chance of contamination and induces changes in the sample environment.…”
Section: Introductionmentioning
confidence: 99%
“…Related electrocatalytic studies have shown that Pt(111) undergoes partial surface reconstruction under applied bias . Potential cycling in acidic electrolytes leads to formation of Pt islands mostly composed of (110) and (100) facets resulting in an increased H 2 evolution activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations